Question
upstudy study bank question image url

9. The graphs of \( a x+b y=18 \) and \( a x-b y=6 \) intersect at \( (3,-2) \). Find \( a \) and \( b \).

Ask by Kelly Harmon. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( a = 4 \) and \( b = -3 \).

Solution

To find the values of \( a \) and \( b \), we can use the given intersection point \( (3, -2) \) in the equations of the lines. Given equations: 1. \( ax + by = 18 \) 2. \( ax - by = 6 \) Substitute the values of \( x = 3 \) and \( y = -2 \) into the equations: 1. \( a(3) + b(-2) = 18 \) 2. \( a(3) - b(-2) = 6 \) Simplify the equations: 1. \( 3a - 2b = 18 \) 2. \( 3a + 2b = 6 \) Now, we have a system of linear equations. We can solve this system to find the values of \( a \) and \( b \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3a-2b=18\\3a+2b=6\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}a=\frac{18+2b}{3}\\3a+2b=6\end{array}\right.\) - step2: Substitute the value of \(a:\) \(3\times \frac{18+2b}{3}+2b=6\) - step3: Simplify: \(18+4b=6\) - step4: Move the constant to the right side: \(4b=6-18\) - step5: Subtract the numbers: \(4b=-12\) - step6: Divide both sides: \(\frac{4b}{4}=\frac{-12}{4}\) - step7: Divide the numbers: \(b=-3\) - step8: Substitute the value of \(b:\) \(a=\frac{18+2\left(-3\right)}{3}\) - step9: Calculate: \(a=4\) - step10: Calculate: \(\left\{ \begin{array}{l}a=4\\b=-3\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}a=4\\b=-3\end{array}\right.\) - step12: Rewrite: \(\left(a,b\right) = \left(4,-3\right)\) The values of \( a \) and \( b \) are \( a = 4 \) and \( b = -3 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the values of \( a \) and \( b \), we start by substituting the point of intersection \( (3, -2) \) into both equations. 1. For the first equation \( ax + by = 18 \): \[ a(3) + b(-2) = 18 \implies 3a - 2b = 18 \quad (1) \] 2. For the second equation \( ax - by = 6 \): \[ a(3) - b(-2) = 6 \implies 3a + 2b = 6 \quad (2) \] Now, we solve the system of equations formed by (1) and (2): From equation (1): \[ 3a - 2b = 18 \] From equation (2): \[ 3a + 2b = 6 \] Next, we can add both equations to eliminate \( b \): \[ (3a - 2b) + (3a + 2b) = 18 + 6 \] \[ 6a = 24 \quad \Rightarrow \quad a = 4 \] Now, we substitute \( a = 4 \) back into one of the original equations to solve for \( b \). Using equation (2): \[ 3(4) + 2b = 6 \] \[ 12 + 2b = 6 \quad \Rightarrow \quad 2b = 6 - 12 \] \[ 2b = -6 \quad \Rightarrow \quad b = -3 \] Thus, the values are \( a = 4 \) and \( b = -3 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy